MODEL PEMBELAJARAN MARKET PLACE ACTIVITY (MPA) DALAM MENINGKATKAN HASIL BELAJAR BIOLOGI - Anugrah Sari; Misykat Malik Ibrahim; Ridwan Idris (Jurnal Biotek, 2021)
The objectives of this study are to 1) describe the application of the learning model of Market Place Activity (MPA) in biology materials and 2) describe the advantages and disadvantages of the learning models. It was a literature study (library research) of the systematic literature review (SLR) type. There were three stages used in this review: 1). Identification. All the articles searched by Google Scholar, ResearchGate, and Academia databases. There were 158 articles found across all databases. 2). The screening process. After screening the identified articles, there were 38 of them. 3). Eligibility. The feasibility determined with the inclusion criteria to achieve five articles. It appears that the application of the learning model of Market Place Activity MPA) can facilitate activities and improve students' biology learning outcomes. Even though the learning model can enhance the student's ability to become active, it is time-consuming. This study suggests that the classroom can run effectively and efficiently if the applied model meets the needs of learning and timing.